2021
DOI: 10.1126/sciadv.abg9739
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic formation of amorphous carbon by anaerobic methanotrophs and select methanogens

Abstract: Elemental carbon exists in different structural forms including graphite, diamond, fullerenes, and amorphous carbon. In nature, these materials are produced through abiotic chemical processes under high temperature and pressure but are considered generally inaccessible to biochemical synthesis or breakdown. Here, we identified and characterized elemental carbon isolated from consortia of anaerobic methanotrophic archaea (ANME) and sulfate-reducing bacteria (SRB), which together carry out the anaerobic oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…As such, the ANME may produce their own PC analogues to facilitate EET. As the amorphous carbon produced by ANME was found to contain redox-active functional groups, such as CO, the positive correlation between the CO content of PC and the kinetics of iron-dependent AOM revealed in this study supports this hypothesis. Given that EET is key to the ability of ANME to couple AOM to a range of different electron acceptors, including sulfate, iron, and manganese oxides and humic substances, PC and PC analogues produced by ANME could have a substantial impact on several processes that link the methane cycle with other global biogeochemical cycles.…”
Section: Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As such, the ANME may produce their own PC analogues to facilitate EET. As the amorphous carbon produced by ANME was found to contain redox-active functional groups, such as CO, the positive correlation between the CO content of PC and the kinetics of iron-dependent AOM revealed in this study supports this hypothesis. Given that EET is key to the ability of ANME to couple AOM to a range of different electron acceptors, including sulfate, iron, and manganese oxides and humic substances, PC and PC analogues produced by ANME could have a substantial impact on several processes that link the methane cycle with other global biogeochemical cycles.…”
Section: Results and Discussionsupporting
confidence: 79%
“…Allen and colleagues recently reported that ANME can produce amorphous carbon with similar characteristics to disordered graphite. 76 Similar to PC, this material was suggested to potentially serve as a conductive element or as a redox-active electron carrier, facilitating the flow of electrons to terminal electron acceptors or syntrophic partners. As such, the ANME may produce their own PC analogues to facilitate EET.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…For instance, in deep-sea sediments, part of CBC is attributed to dissolved BC (DBC) being adsorbed. Several studies highlight significant uncertainty about the source of DBC in the oceans and explore possible unknown sources, which suggest potential sources (e.g., hydrothermal vents) contributing to both CBC and TOC. Conversely, we have yet to find reports on sources in the ocean that contribute to both SBC and CBC.…”
Section: Discussionmentioning
confidence: 99%
“…Further aggregation of globules leads to the formation of micro-nanosize agglomerates with pores of tens nm and more [52]. Such a structure is typical to natural sp 2 aCs such as shungite carbon, anthraxolite, anthracite, as well as black carbon coating of diamonds [57], mixed carbon-silica spherical 'sweets' [58], black carbon in meteorites [59,60] and metamorphosed polymictic sandstones [61], biogenic carbon, originated from anaerobic oxidation of methane [62], and none of the exclusions have been known so far. Figure 2 presents the evolution of the structure of this kind of sp 2 aC from a single BSU to macroscopic rocks.…”
Section: General Characteristics Of the Carbon Amorphicitymentioning
confidence: 99%